All Binder-Free Electrodes for High-Performance Wearable Aqueous Rechargeable Sodium-Ion Batteries - He, Bing; Man, Ping; Zhang, Qichong; Fu, Huili; Zhou, Zhenyu; Li, Chaowei; Li, Qiulong; Wei, Lei; Yao, Yagang (Nano-Micro Letters, 2019)
Extensive efforts have recently been devoted to the construction of aqueous rechargeable sodium-ion batteries (ARSIBs) for large-scale energy-storage applications due to their desired properties of abundant sodium resources and inherently safer aqueous electrolytes. However, it is still a significant challenge to develop highly flexible ARSIBs ascribing to the lack of flexible electrode materials. In this work, nanocube-like KNiFe(CN)6 (KNHCF) and rugby ball-like NaTi2(PO4)3 (NTP) are grown on carbon nanotube fibers via simple and mild methods as the flexible binder-free cathode (KNHCF@CNTF) and anode (NTP@CNTF), respectively. Taking advantage of their high conductivity, fast charge transport paths, and large accessible surface area, the as-fabricated binder-free electrodes display admirable electrochemical performance. Inspired by the remarkable flexibility of the binder-free electrodes and the synergy of KNHCF@CNTF and NTP@CNTF, a high-performance quasi-solid-state fiber-shaped ARSIB (FARSIB) is successfully assembled for the first time. Significantly, the as-assembled FARSIB possesses a high capacity of 34.21 mAh cm−3 and impressive energy density of 39.32 mWh cm−3. More encouragingly, our FARSIB delivers superior mechanical flexibility with only 5.7% of initial capacity loss after bending at 90° for over 3000 cycles. Thus, this work opens up an avenue to design ultraflexible ARSIBs based on all binder-free electrodes for powering wearable and portable electronics. Highlights: 1 Nanocube-like KNiFe(CN)6 and rugby ball-like NaTi2(PO4)3 are grown on carbon nanotube fibers via simple and mild methods. 2 A quasi-solid-state fiber-shaped aqueous rechargeable sodium-ion battery based on all binder-free electrodes is successfully assembled for the first time, delivering a high volumetric capacity of 34.21 mAh cm−3 and impressive volumetric energy density of 39.32 mWh cm−3. 3 The device delivers superior mechanical flexibility with only 5.7% of initial capacity loss after bending at 90° for over 3000 cycles.